2020
DOI: 10.1101/2020.03.13.990036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ocular conjunctival inoculation of SARS-CoV-2 can cause mild COVID-19 in Rhesus macaques

Abstract: 19 The outbreak of Corona Virus Disease 2019 caused by the severe acute respiratory 20 syndrome coronavirus (SARS-CoV-2) is highly transmitted. The potential 21 extra-respiratory transmission routes remain uncertain. Five rhesus macaques were 22 inoculated with 1×10 6 TCID50 of SARS-CoV-2 via conjunctival (CJ), intratracheal 23 (IT), and intragastric (IG) routes, respectively. Remarkably, the CJ 24 inoculated-macaques developed mild interstitial pneumonia and viral load was 25 detectable in the conjunctival sw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 7 publications
6
125
0
1
Order By: Relevance
“…Although the main mode of SARS-CoV-2 transmission is predominantly respiratory, several studies have suggested that exposure of unprotected eyes to the virus may also cause novel coronavirus pneumonia (NCP) [1,2]. In agreement, a recent animal study also confirmed that macaque's conjunctiva inoculated with SARS-CoV-2 lead to the development of mild interstitial pneumonia [3], implying that ocular tissues and fluid may be a potential alternative mode of SARS-CoV-2 transmission. So far, there have been varying reports regarding the prevalence of ocular manifestations among COVID-19-infected patients [2,[4][5][6][7][8][9].…”
Section: Dear Editormentioning
confidence: 77%
“…Although the main mode of SARS-CoV-2 transmission is predominantly respiratory, several studies have suggested that exposure of unprotected eyes to the virus may also cause novel coronavirus pneumonia (NCP) [1,2]. In agreement, a recent animal study also confirmed that macaque's conjunctiva inoculated with SARS-CoV-2 lead to the development of mild interstitial pneumonia [3], implying that ocular tissues and fluid may be a potential alternative mode of SARS-CoV-2 transmission. So far, there have been varying reports regarding the prevalence of ocular manifestations among COVID-19-infected patients [2,[4][5][6][7][8][9].…”
Section: Dear Editormentioning
confidence: 77%
“…At the time of writing, there are no animal models that truly mimic the disease spectrum and pathogenesis of COVID-19. However, small animals (e.g., human ACE2 transgenic laboratory mice (19), cats (20), domestic ferrets (20, 21), golden hamsters (22)), and nonhuman primates (e.g., rhesus monkeys (23, 24), crab-eating macaques (25)), are used to study SARS-CoV-2 infection as alveolar damage, interstitial inflammation, and viral shedding occur in these animal models to various degree. It is hoped that further development of these and other animal models will help overcome the current roadblock to evaluating the efficacy of candidate medical countermeasures (MCMs) against and the pathogenesis of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…However, an as yet non-peer-reviewed paper has been made available that directly compares inoculation of SARS-CoV-2 of rhesus macaque monkeys via their conjunctiva, trachea or stomach. 51 While the one monkey that received SARS-CoV-2 via their trachea had weight loss, the two monkeys that were inoculated via their conjunctiva had no weight loss. SARS-CoV-2 RNA was transiently found in the conjunctiva after one day only, and only in conjunctivainfected monkeys.…”
Section: Animal Studies Of Human Coronavirus Infectionmentioning
confidence: 99%
“…The authors concluded that conjunctival inoculation resulted in a mild lung infection compared to the trachea inoculation. 51 Unfortunately, no histology was performed on the eye during the infection, and given…”
Section: Animal Studies Of Human Coronavirus Infectionmentioning
confidence: 99%